Cultural interaction and biological distance in postclassic period Mexico. Issue 1 (20th January 2015) - Ragsdale, Corey S.; Edgar, Heather J.H.
ABSTRACT Economic, political, and cultural relationships connected virtually every population throughout Mexico during Postclassic period (AD 900–1520). Much of what is known about population interaction in prehistoric Mexico is based on archaeological or ethnohistoric data. What is unclear, especially for the Postclassic period, is how these data correlate with biological population structure. We address this by assessing biological (phenotypic) distances among 28 samples based upon a comparison of dental morphology trait frequencies, which serve as a proxy for genetic variation, from 810 individuals. These distances were compared with models representing geographic and cultural relationships among the same groups. Results of Mantel and partial Mantel matrix correlation tests show that shared migration and trade are correlated with biological distances, but geographic distance is not. Trade and political interaction are also correlated with biological distance when combined in a single matrix. These results indicate that trade and political relationships affected population structure among Postclassic Mexican populations. We suggest that trade likely played a major role in shaping patterns of interaction between populations. This study also shows that the biological distance data support the migration histories described in ethnohistoric sources. Am J Phys Anthropol 157:121–133, 2015. © 2015 Wiley Periodicals, Inc.